Analisis Perbedaan Tingkat Kelulusan Computer Based Test Uji Kompetensi Mahasiswa Program Profesi Dokter Berdasarkan Tingkat Kehadiran pada Kegiatan Pembekalan di Fakultas Kedokteran Universitas Riau - Firdaus Firdaus; Chairunnisa Chairunnisa; Rita Endriani (Fakultas Kedokteran Universitas Riau, 2021)
Tutoring of UKMPPD is a preparation effort in the form of tutoring activities to get more optimal understanding and results for UKMPPD. The purpose of the research was to analyze the differences in the pass rates of UKMPPD-CBT based on attendance levels in the UKMPPD tutoring activities at the Medical Faculty of Riau University. The design of this research was a comparative analytic with a retrospective approach. The result was using Mann Whitney U Test obtained sig (2-tailed) 0.010 (<0.05), it showed there was a significant difference between the results of passing UKMPPD-CBT for the group that took the tutoring and the group that did not take the tutoring. The research also used the Kruskall Wallis analysis test and obtained sig (2-tailed) 0.000 (<0.05), it showed there was a significant difference between the UKMPPD-CBT passing results and the attendance level of first taker students in UKMPPD tutoring activities.